CONSUMO REGIONAL DE PSICOTRÓPICOS NOS ANOS DE 2004 E 2005: PERFIS DE CONSUMO E DIFERENÇAS SEXUAIS - CHRISTMANN, MORGANA; FRANCO, LUIS F.; HANAUER, THEO; HANAUER, THOMAS; MEINEM, ANA L. F.; OLINHG, RUBIA; DIETZ, GRACIELE; SOARES, FERNANDO V.; NONNEMACHER, CARINE L.; RABUSKE, ALESSANDRO A.; et al. (Salão do Conhecimento, 2013)
Resumo